A retrospective study of dyslipidaemia in patients with chronic kidney disease at Charlotte Maxeke Johannesburg Academic Hospital - Essop, Mohammed Rafique (My University, 2022)
Background Atherosclerotic cardiovascular disease (ASCVD) is a major cause of morbidity and mortality in patients with chronic kidney disease (CKD), whilst CKD itself is considered a coronary artery disease equivalent due to its atherogenic potential. Despite the role of CKD in ASCVD and recommendations to control lipid levels aggressively, landmark lipid studies have often excluded patients with CKD. Furthermore, there is little to no data examining the use and efficacy of lipid lowering therapy (LLT) in those with CKD in South Africa. We therefore undertook this study to further examine the prevalence and control of dyslipidaemia in a cohort of South African patients with CKD. Methods A retrospective, cross-sectional observational study of 250 patients with CKD attending the Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) renal clinic from 1 July 2019 to 31 July 2020. Lipograms, the use of lipid lowering therapy (LLT) and achievement of target lipid levels were examined. Results The median age of this cohort was 58 years (46-69, 95% CI); 50.4% were males and 64.4% were black African. The prevalence of dyslipidaemia in this study was 83.6% (N=209). Of the 250 patients enrolled 169 (67.6%) were on LLT, of these just 28 (16.6%) achieved the recommended low-density lipoprotein cholesterol (LDL-C) target. Of those not on LLT, 51 (63%) were eligible for LLT and almost all were classified as either very high risk (64.2%) or high risk (28.4%). Of those on LLT, all were on statin therapy, of which simvastatin at a mean dose of 21.2mg was the most commonly prescribed LLT. Conclusion This cohort comprised a large proportion of patients classified as high or very high risk by European Society of Cardiology criteria. Despite this, the use of LLT was inadequate and less than 20% of patients were at target LDL-C levels. These data suggest a greater need for awareness of initiating statin therapy and achieving target LDL-C levels in patients with CKD.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Medicine in Internal Medicine to the Faculty of Health Sciences, School of Clinical Medicine, University of Witwatersrand, Johannesburg, 2022